Exosomal noncoding RNAs in central nervous system diseases: biological functions and potential clinical applications - Wang, Zhong-Yu; Wen, Zeng-Jin; Xu, Hai-Ming; Zhang, Yu; Zhang, Yin-Feng (Frontiers in Molecular Neuroscience, 2022)
Central nervous system (CNS) disease is a general term for a series of complex and diverse diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), multiple sclerosis (MS), CNS tumors, stroke, epilepsy, and amyotrophic lateral sclerosis (ALS). Interneuron and neuron-glia cells communicate with each other through their homeostatic microenvironment. Exosomes in the microenvironment have crucial impacts on interneuron and neuron-glia cells by transferring their contents, such as proteins, lipids, and ncRNAs, constituting a novel form of cell-to-cell interaction and communication. Exosomal noncoding RNAs (ncRNAs), including microRNAs (miRNAs), long noncoding RNAs (lncRNAs), circular RNAs (circRNAs), and PIWI-interacting RNAs (piRNAs), regulate physiological functions and maintain CNS homeostasis. Exosomes are regarded as extracellular messengers that transfer ncRNAs between neurons and body fluids due to their ability to cross the blood-brain barrier. This review aims to summarize the current understanding of exosomal ncRNAs in CNS diseases, including prospective diagnostic biomarkers, pathological regulators, therapeutic strategies and clinical applications. We also provide an all-sided discussion of the comparison with some similar CNS diseases and the main limitations and challenges for exosomal ncRNAs in clinical applications.